SUGAR CANE AGRIBUSINESS MARKETING ANALYSIS ON DRY LAND PEOPLE IN NGAWI DISTRICT, EAST JAVA, INDONESIA (Special review of farmers' share price, the price transmission elasticity, and market integrated, and so the structure of the people sugar market) - Agus Santosa (UPT Penerbitan Universitas Jember, 2012)
The purposes of the research are to analyze the people’s cane marketing activities covering: (1) margin analysis and farmer‘s price share, (2) analysis of price transmissionelasticity and market integration, and also (3) analysis of established market structure. Theresearch is brought about in cane-farming-on-dry-land in the district of Ngawi, which ischosen with purposive sampling, then the sub district of Pitu as representation of theDistrict of Ngawi is also picked up with purposive sampling, while as the sites of theresearch, two villages namely Ngancar and Papungan are taken with simple randomsampling method. In current research 87 farmers for sample are obtained with stratifiedrandom sampling method. The traders chosen as sample are decided with purposivesampling considering that the traders chosen can represent the trader population and it isintended to avoid repeated sampling on the same traders. In this research, 25 retailers fromabout 85 retailers and 10 wholeslers from total 36 wholesalers in Ngawi are sampled. From87 farmer in the sample, all their cane crops are collected by 25 retailers and 10wholesalers chosen, so that it is expected that traders in the sample can represent otherretailers and wholesalers in Ngawi. The results of the research show that (1) in marketingprocess phase show that the longer the cane marketing chain (the first and the secondmarketing pattern) make the marketing margin the larger so the lower farmer’s share price,(2) the longer the cane marketing chain , the lower the transmission elasticity (not quiteperfect) and market integrity occurs in the long run, which makes the marketing patternless efficient,(3) on the short chained marketing pattern (the third marketing pattern) tendsto make the marketing margin narrower, the farmer price share gets larger, the pricetransmission elasticity gets higher (perfect) and market integrity occurs in the short run(ideal for cane marketing), and it all means that marketing pattern will be relatively moreefficient.